SAT0678 Seasonality of new early inflammatory arthritis cases: preliminary results from the canadian early arthritis cohort. (12th June 2018) - Kudaeva, F.; Speechley, M.; Klar, N.; Schieir, O.; Bartlett, S.; Hitchon, C.; Boire, G.; Haraoui, B.; Keystone, E.; Tin, D.; Thorne, C.; Bykerk, V.; et al.
Abstract : Background: Disease clustering suggests a possible environmental cause. However, confirming the causes of time-place clustering is challenging. Rheumatoid arthritis (RA) is an autoimmune disease that may be triggered by environmental factors: viral or bacterial infections can lead to RA via molecular mimicry, epitope spreading, B-cell-mediated pathway, bystander activation and via superantigens. Putative infections may also cluster. Objectives: To study the seasonal distribution of early inflammatory arthritis (IA) onsets in a Canadian sample, and potential relationships with influenza (flu) outbreaks. Methods: Data from an incidence cohort of adults (>18 years) with early IA with <13 months symptom duration from the Canadian Early Arthritis Cohort (CATCH) enrolled between January 2007 – January 2017. Patient-reported date of symptom onset and physician-reported date of IA onset were used to estimate the monthly frequency of early inflammatory arthritis onsets. Monthly flu case frequencies from September 2010 – December 2016 were retrieved from the Public Health Agency of Canada's FluWatch national surveillance system of confirmed influenza A and B cases. Time-series Poisson regression analyses were performed to assess the non-random covariance of IA and flu with different hypothesised time lags. Results: A total of 2262 with early IA were included. Patient-reported IA onset was more frequent in winter months compared to other seasons (p=0.002), with peaks in January (figure 1). The ten-year aggregated data also showed January peaks of IA onset. There was a positive linear correlation between the number of IA and influenza A onsets (r=0.23, p=0.045), and almost no relationship between the number of IA and influenza B cases (p=0.87) (figure 2). Conclusions: Our study provides novel information on the increased onset of IA in relation to seasonal influenza patterns in a Canadian population and adds to the existing literature supporting viral infections as a possible trigger to RA onset. Disclosure of Interest: None declared